Optimal structure in interconnected dynamical systems (I) - Fausto Posso (Revista Técnica de la Facultad de Ingeniería, 2011)
In this paper we study the modeling of interconnected dynamical systems (SDI), under the structural approximation “Component-Connection Model” (CCM). It tries specially the existence of the composite model and his relation with CCM. It has been found that certain structures of connection of SDI, so called “hierarchical structures” predict “a priori” the existence of the composite model and also it is possible to obtain important simplifications both conceptual and numerical on the solution phase of the model. We propose and develop an algorithm to obtain a hierarchical structure based on an arbitrary connection structure. This algorithm is based on graph theory and it is applied with success on two bibliographical examples.